Sistem Pengolahan Data Pasien Berbasis Web - Agung Wahana; Asep Ririh Riswaya (Jurnal Computech & Bisnis (e-Journal), 2015)
The research objective is to create a data processing system of the patient using the web. This system was made because of the system that runs the data processing still using semi- computerized, so that the processing of patient data require considerable time and less efficient. With patient data processing system is expected to help the company to improve patient care as well as to store data or other important documents that must be kept so well that in the presentation of information to be fast and accurate . Method of application development on credit payments are made using SDLC (System Development Life Cycle). Implementation of the program using the programming language by using PHP as the programming language, MySQL as database processing, Apache2triad as a web server, PHP editor and Wscite as Adobe Photoshop as image processing. Keywords: data processing system; web based